Designing Community Complaints and Disaster Reporting Application to Babinsa Based on IOS - Syauqiyah, Khansa Ghazalah; Nurdin, Ali; Handayani, Ade Silvia (Universitas Negeri Padang, 2024)
The role of telecommunications in facilitating communication and information exchange is very important, especially in emergencies such as natural disasters and unexpected events in the community. The application of mobile technologies such as apps is an alternative to improve response and address such issues. Mobile technology allows people to easily report disaster events or security issues through apps or short message services. The application of this technology supports faster communication between the community and Babinsa. Communities can quickly submit reports, convey important information, and share photos or videos as evidence of events. The reporting application is an implementation of mobile technology that can be more efficient in responding to reports and taking the necessary actions based on the information received to facilitate two-way communication between officers and the community. This research was conducted to develop an application that can facilitate the community and babinsa in responding to an event more efficiently, the results of this development prove that the application has an efficiency level of around 75% and also the learnability level reaches 80% which indicates that the application is ready to be launched to the general public and can be easily used for all groups.